2019
DOI: 10.1088/1361-6528/ab1866
|View full text |Cite
|
Sign up to set email alerts
|

Defect influence on in-plane photocurrent of InAs/InGaAs quantum dot array: long-term electron trapping and Coulomb screening

Abstract: Metamorphic InAs/In 0.15 Ga 0.85 As and InAs/In 0.31 Ga 0.69 As quantum dot (QD) arrays are known to be photosensitive in the telecommunication ranges at 1.3 and 1.55 μm, respectively; however, for photonic applications of these nanostructures, the effect of levels related to defects still needs in-depth investigation. We have focused on the influence of electron traps of defects on photocurrent (PC) in the plane of the QD array, studying by PC and deep level thermally stimulated current spectroscopy together … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 87 publications
3
26
2
Order By: Relevance
“…Moreover, in the case of MoS 2 on an n-type SiO 2 /Si substrate, the local electric field of the vdW interface can be substantially enhanced by the Coulomb screening originated on the interface with the n-type substrate (Figure ). , At that time, more photogenerated electrons accumulate at the vdW interface so that their wavefunctions overlap better, enhancing the probability to form the trions. On the other hand, when increasing the number of layers, the MoS 2 conduction band lowers with respect to the vacuum level, thus prompting the substrate-to-MoS 2 charge transfer effect and further localization of these electrons in the quantum well .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Moreover, in the case of MoS 2 on an n-type SiO 2 /Si substrate, the local electric field of the vdW interface can be substantially enhanced by the Coulomb screening originated on the interface with the n-type substrate (Figure ). , At that time, more photogenerated electrons accumulate at the vdW interface so that their wavefunctions overlap better, enhancing the probability to form the trions. On the other hand, when increasing the number of layers, the MoS 2 conduction band lowers with respect to the vacuum level, thus prompting the substrate-to-MoS 2 charge transfer effect and further localization of these electrons in the quantum well .…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, the disappearance of the FKOs at the low temperature regime indicates that there must be some dominant opposing field to the existing built-in electric field for these structures. These experimentally observed results can be understood from the change in energy band bending profile due to the localized charge carriers at the hetero-junctions as illustrated with the dotted lines in the schematic shown in figure 5(d) [36,37]. At low temperatures, the charge carriers do not possess sufficient thermal energy to come out from the localized energy states and the corresponding change in energy band bending profile results in higher contribution of electric field due to the interfaces E i .…”
Section: Resultsmentioning
confidence: 87%
“…Most researchers to date focused on the vertical In(Ga)As QDIPs, proposing the mechanisms of PC and analyzing current dependences on bias voltage, frequency, temperature and excitation intensity [27][28][29][30][31][32]. Despite the potential for applications, the lateral processes are not well studied, and not so many studies for the in-plane PC in In(Ga)As QD arrays have been reported [24,25,[33][34][35][36][37]. In particular, we have reported previously efficient interband QD PC for the lateral nanostructures highly sensitive to low-intense radiation and having nonlinear dependence of PC on light intensity [24,25,36], interdot tunneling and hopping conduction [38].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we have reported previously efficient interband QD PC for the lateral nanostructures highly sensitive to low-intense radiation and having nonlinear dependence of PC on light intensity [24,25,36], interdot tunneling and hopping conduction [38]. Furthermore, defect and interface levels have been shown to be strongly involved in the PC mechanism as well as dark conductivity, acting as carrier traps and/or nonradiative recombination centers and providing substantial impact on the photoresponse [33,35,39]. Many aspects of the deep level involvement in the photoresponse mechanism still remain unclear, despite the fact that the control of defect density is crucial to achieve sensitive sensors or efficient emitters [33,40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation